Evaluating the impact of public-private partnerships-enabling conditions on infrastructure development: Evidence from Latin America and the Caribbean - Carter Boon Casady; Ancor Suárez-Alemán (Inter-American Development Bank (IDB), 2025)
This paper investigates the impact of public-private partnership (PPP)-enabling conditions on infrastructure development in Latin America and the Caribbean (LAC). Using a unique longitudinal dataset, this study analyzes how institutional conditions in 26 LAC countries influenced PPP investment activity between 2009 and 2022. The findings indicate political and social will, along with institutional capacity, are significant predictors of PPP investment, while market reliability, transparency, governance mechanisms, and regulatory regimes, although important, are less impactful. These findings highlight the critical importance of political stability and strong institutional frameworks in driving PPP investment activity in the region.
Keywords: 330; Infrastructure development; Public-private partnerships (PPP); Latin America and the Caribbean; Institutional capacity; Political and social will